Konstruksi Reforma Pajak Bagi Pemilik Tanah Dati Di Kota Ambon Dalam Perspektif Keadilan - Ronald Saija; Nancy Silvana Haliwela; Triska Demmatacco (AIWADTHU: Jurnal Pengabdian Hukum, 2023)
Introduction: The land owner does not have real and legal evidence that has legal force, so Village Officials assume that the land still belongs to the village and can be given or sold by the Village.Purposes of Devotion: This service can produce a legal product in the form of a state regulation and even state regulations regarding the construction of tax reform for dati landowners in the perspective of justice, so that dati landowners can know the tax collection model that can be used as proof of tax payment so that there is proof of ownership that is legally and has legal protection for dati landowners. Method of Devotion: The implementation of this service uses the extension method, through discussion in which the presenter explains material related to the service and is followed by questions and answers between the presenter and the participants.Results of the Devotion: The owner of the Dati lands in Soya Village is state land granted by the Official, so it is necessary to prove ownership of the land under Indonesian law so that it does not become a dispute in the future, the speaker provides information regarding the payment of Land and Building Tax to protect the rights of the villagers including the ulayat rights of indigenous peoples, especially the owners of dati lands. In fact, the land owner in Soya Village has never paid his land tax (traditional land tax) to the tax office related to land tax or regional tax due to the lack of information and understanding regarding the Tax Payment Model which can be used or as proof of ownership and can be used as legal protection in the event of a dispute in the future. As for the gap, namely whether the form of tax reform construction can cover the process of paying taxes on customary lands in Ambon City. in accordance with state regulations in order to create justice.